Association between mental health symptoms and behavioral performance in younger vs. older online workers - Mills-Finnerty, Colleen; Staggs, Halee; Hogoboom, Nichole; Naparstek, Sharon; Harvey, Tiffany; Beaudreau, Sherry A.; O’Hara, Ruth (Frontiers in Psychiatry, 2023)
Background The COVID-19 pandemic has been associated with increased rates of mental health problems, particularly in younger people. Objective We quantified mental health of online workers before and during the COVID-19 pandemic, and cognition during the early stages of the pandemic in 2020. A pre-registered data analysis plan was completed, testing the following three hypotheses: reward-related behaviors will remain intact as age increases; cognitive performance will decline with age; mood symptoms will worsen during the pandemic compared to before. We also conducted exploratory analyses including Bayesian computational modeling of latent cognitive parameters. Methods Self-report depression (Patient Health Questionnaire 8) and anxiety (General Anxiety Disorder 7) prevalence were compared from two samples of Amazon Mechanical Turk (MTurk) workers ages 18–76: pre-COVID 2018 (N = 799) and peri-COVID 2020 (N = 233). The peri-COVID sample also completed a browser-based neurocognitive test battery. Results We found support for two out of three pre-registered hypotheses. Notably our hypothesis that mental health symptoms would increase in the peri-COVID sample compared to pre-COVID sample was not supported: both groups reported high mental health burden, especially younger online workers. Higher mental health symptoms were associated with negative impacts on cognitive performance (speed/accuracy tradeoffs) in the peri-COVID sample. We found support for two hypotheses: reaction time slows down with age in two of three attention tasks tested, whereas reward function and accuracy appear to be preserved with age. Conclusion This study identified high mental health burden, particularly in younger online workers, and associated negative impacts on cognitive function.